Establishing a long-term permanent plot in remnant forest of Cibodas Botanic Garden, West Java - ZAENAL MUTAQIEN; MUSYAROFAH ZUHRI (Society for Indonesian Biodiversity, 2011)
Mutaqien Z, Zuhri M (2011) Establishing a long-term permanent plot in remnant forest of Cibodas Botanic Garden, West Java. Biodiversitas 12: 218-224. Cibodas Botanic Garden (CBG) has unique characters; almost 10% of which is forested area adjacent to the natural forest of Mt. Gede Pangrango National Park. The area is a transition between natural forest and artificial habitat which mostly consists of exotic plant species. The permanent plot in CBG was established in 2007-2009. Two hundred and eighty four units of 10x10 square meters sub-plot were established in four locations, i.e. Wornojiwo, Kompos, Jalan Akar, and Lumut forest. Vegetation analyses were conducted for trees, saplings, shrubs, and herb species. The inventory found 137 species plants consisting of 74 tree speciesdominated by Villebrunea rubescens (Bl.) Bl. and Ostodes paniculata Bl., 30 shrub species dominated by Strobilanthes hamiltoniana (Steud.), 24 herb species dominated by Cyrtandra picta Bl., 6 fern species mainly consisted of Diplazium pallidum Moore, and 3 climber species dominated by Calamus reinwardtii Mart. In comparison with the natural forest of Mt. Gede Pangrango National Park, the CBG permanent plot showed a good representative of the vegetation of lower montane forest. A regular monitoring during the successive years is needed to maintain diversity, monitor forest dynamics and anticipate the spread of invasive plant from CBG.